Proceedings of the 1984 ACM Symposium on LISP and Functional Programming - LFP '84 1984
DOI: 10.1145/800055.802040
|View full text |Cite
|
Sign up to set email alerts
|

Garbage collection in a large LISP system

Abstract: This paper discusses garbage collection techniques used in a high-performance Lisp implementation with a large virtual memory, the Symbolics 3600. Particular attention is paid to practical issues and experience. In a large system problems of scale appear and the most straightforward garbagecollection techniques do not work well. Many of these problems involve the interaction of the garbage collector with demand-paged virtual memory. Some of the solutions adopted in the 3600 are presented, including incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 213 publications
(58 citation statements)
references
References 6 publications
0
57
0
Order By: Relevance
“…Moon describes a modification to this algorithm that results in approximate depth-first copying [18]. Wilson et al further refine the traversal to obtain hierarchical grouping of objects in TO space [30].…”
Section: Combining Cache-conscious Data Placement With Garbage Collecmentioning
confidence: 99%
See 2 more Smart Citations
“…Moon describes a modification to this algorithm that results in approximate depth-first copying [18]. Wilson et al further refine the traversal to obtain hierarchical grouping of objects in TO space [30].…”
Section: Combining Cache-conscious Data Placement With Garbage Collecmentioning
confidence: 99%
“…Researchers investigated two approaches to using a garbage collector to improve paging behavior of Smalltalk and LISP systems [18,30,15,10]. Static regrouping [18,30] uses the topology of heap data structures to rearrange structurally-related objects, while dynamic regrouping [10] clusters objects according to a program's data access pattern. Moon [18] found that depth-first copying generally yields better virtual memory performance than breadth-first copying for LISP, because it is more likely to place parents and offspring on the same page, particularly if data structures tend to be shallow, but wide.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, realtime garbage techniques are not suitable for such a machine. Real-time garbage collection techniques need special purpose hardware such as that found on the Lisp Machine [20] in order to be feasible. Thus, this thesis limits itself to a discussion of "stop the world" techniques.…”
Section: Background and Assumptionsmentioning
confidence: 99%
“…The copying algorithm as presented in this chapter traverses and copies the graph of accessible objects in a breadth-first fashion. Moon [20] argues that, for Lisp, depth-first copying yields better locality than breadth-first copying. He suggests a method of copying called approximate depth-first copying, which uses depth-first copying on partially filled pages of to-space.…”
Section: Extensions Of the Algorithmmentioning
confidence: 99%